He Asked Me What!?—Using Shared Online Accounts as Training Tools for Distance Learning Librarians. Issue 1 (2nd January 2017) - Robinson, Kelly; Casey, Anne Marie; Citro, Kathleen
ABSTRACT: This study explores the idea of creating a knowledge base from shared online accounts to use in training librarians who perform distance reference services. Through a survey, follow-up interviews and a case study, the investigators explored current and potential use of shared online accounts as training tools. This study revealed that the participants viewed the concept positively, but many encountered barriers to effectively employing a local knowledge base as a training tool.